2003
DOI: 10.1029/2002jb001916
|View full text |Cite
|
Sign up to set email alerts
|

Melting processes and fluid and sediment transport rates along the Alaska‐Aleutian arc from an integrated U‐Th‐Ra‐Be isotope study

Abstract: [1] A comprehensive data set for young lavas erupted along the Alaska-Aleutian arc is used to examine how fluid and sediment transport rates and melting processes vary in response to systematic changes in subduction rate and dip along the arc and across the ocean-continent boundary. Positive correlations between convergence rate, volcano volume, and 238 U excesses suggest that magmatic output is closely linked to the size of the fluid flux which occurred <10 kyr prior to eruption. Sediment-sensitive tracers li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 117 publications
5
90
2
Order By: Relevance
“…Our uncertainty as 9% (1σ) is larger than that reported in George et al (2003). Our uncertainty, however, may include heterogeneous distribution of 10 Be and it is not clear if it can be compared with that reported in George et al (2003) directly.…”
Section: Error Associated With Each Results Was Calculated As Describecontrasting
confidence: 47%
See 2 more Smart Citations
“…Our uncertainty as 9% (1σ) is larger than that reported in George et al (2003). Our uncertainty, however, may include heterogeneous distribution of 10 Be and it is not clear if it can be compared with that reported in George et al (2003) directly.…”
Section: Error Associated With Each Results Was Calculated As Describecontrasting
confidence: 47%
“…They reported reproducibility of 10 Be/ 9 Be ratio as less than 22%. George et al (2003) reported that reproducibility on 10 Be measurements are typically 5% (1σ) at concentrations >1 × 10 6 atoms g -1 without detailed descriptions. Our uncertainty as 9% (1σ) is larger than that reported in George et al (2003).…”
Section: Error Associated With Each Results Was Calculated As Describementioning
confidence: 99%
See 1 more Smart Citation
“…REE fractionation patterns can reflect the nature of the mantle source and the extent of melting (George et al, 2003). Despite the uncertainties related to the possible accumulation of pyroxene and the choice of clinopyroxene-melt partition coefficients, we conclude that the REE patterns of equilibrium melts (Figs.…”
Section: Shallow Melting Depthmentioning
confidence: 97%
“…Both the Sm/La and Nb/Ce of Group-I dykes fall either within or very close to the data range of basalt/ dolerites of active continental margins. High Th/Nb ratio of Group-I dykes compared to Group II dykes suggests the involvement of partial melt of subducted sediments (Class et al, 2000;George et al, 2003;Plank, 2005) in Group-I dykes. Although the range of Th/Nb ratios of Group-I dykes matches with that of the active continental margin basalts, it also overlaps with that of IABs.…”
Section: Fig 6 (A) Morb-normalized (After Pearce 1983) Multielementmentioning
confidence: 99%